A Catalyst Platform for Unique Cationic (Co)Polymerization in Aqueous Emulsion1. (27th May 2015) - Vasilenko, Irina V.; Yeong, Hui Yee; Delgado, Marco; Ouardad, Samira; Peruch, Frédéric; Voit, Brigitte; Ganachaud, François; Kostjuk, Sergei V.
Abstract Sodium dodecyl benzene sulfonate (DBSNa) surfactants, with a polydisperse and hyperbranched structure, combined with different rare earth metal salts generate highly water‐dispersible Lewis acid surfactant combined catalysts (LASCs). This platform of new complexes promotes fast, efficient cationic polymerization of industrially relevant monomers in direct emulsion at moderate temperature. The process described here does not require high shearing, long polymerization time, or large catalyst content. It allows the reproducible generation of high‐molar‐mass homopolymers of pMOS, styrene, and isoprene, as well as random or multiblock copolymers of the latter two, in a simple and straightforward one‐pot reaction.